The Synodal Path of the Churches in Italy: Learnings and Questions from a National Synodal Process - Zaccaria, Francesco (Concilium, 2026)
The Synodal Path of the Churches in Italy, though closely intertwined with the Universal Synod, has developed as a distinct synodal process for the Italian Church, with its own timeframes, themes, methods, and organizations. This path has led to some progress at the national level in the synodal conversion of the Churches in Italy, such as the ongoing involvement of dioceses and a significant investment of time and resources. However, it has also highlighted some critical issues, such as slowness in defining the path or some opaque steps. The experience of this journey offers some questions for further reflection on the development of synodality within Church groupings, on the creation of new bodies to support and monitor this development, and on the identity and service of experts in ecclesial synodal processes.